Pengembangan Aplikasi Diet Diabetes Melitus Berbasis Android Development of Diet Diabetes Melitus Applications Based On Android - Ferdiana, Suci; Nasir, Muhammad (Infokes, 2017)
There are 383 million people living with diabetes in the world by 2013. In the year 2035 that number will be increased to 592 million. An estimated 383 million of the 175 million people, yet undiagnosed, thus developing progressive threatened to become unwitting complications and without the prevention. This research aims to develop application called Diabetafiq. Diabetafiq is an application how to diet or control the pattern of food diabetics mellitus android based. Process engineering applications using the waterfall process model as a model of the process of application development. Stages of testing on this research was conducted in order to perform verification and validation (V&V) on the application. The process of verification of software testing is done with white box testing is done by the method of basis path testing. The process of validation is performed with black box testing, alpha testing and the test material. Based on the results of research on application developed show results: 1) design of android apps on a diet diet diabetes mellitus as a method or setting the eating patterns of sufferers of diabetes mellitus and applications from design to testing has been in accordance with the specifications; 2) performance of android applications diet diabetes mellitus as a media AIDS community who suffer from diabetes mellitus therapy to run the food is predominantly fall into the category of "highly feasible" with details of test results per factors: functionality 81.90%, 83.11% efficiency, usability and portability 77.11% 100%. Research undertaken researchers still focus on the process of development of diabetes mellitus diet and testing. This research has not been researching about how effective the application of Diabetes mellitus to improve health care quality. Related to this need for further research in the future to find out the level of effectiveness of the application of DM to improve health quality.